2020
DOI: 10.1097/jsm.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Reporting of SCAT-5 Concussion Symptoms in Adolescent Athletes

Abstract: Objective: To elucidate specific symptoms that may differ between adolescent female and male athletes after a sports-related concussion (SRC) and identify symptoms that may require greater clinical attention by medical and athletic staff. Design: Prospective. Setting: This study is part of a larger research project conducted at clinics in the North Texas Concussion Network (ConTex) Registry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Although previous research has found that both sexes exhibit some degree of affective impairment, the consensus of literature states that women experience significantly exacerbated symptoms (Broshek et al, 2005;Sufrinko et al, 2017). Thus, the prevalence of depression, anxiety, and fear is increased in women compared to men (Bunt et al, 2020). Moreover, studies suggest that the severity of behavioral deficits in women depends on their menstrual phase (Bazarian et al, 2010;Stein, 2013;Wunderle et al, 2014).…”
Section: Behavioral Consequences Of Mild Tbimentioning
confidence: 98%
See 3 more Smart Citations
“…Although previous research has found that both sexes exhibit some degree of affective impairment, the consensus of literature states that women experience significantly exacerbated symptoms (Broshek et al, 2005;Sufrinko et al, 2017). Thus, the prevalence of depression, anxiety, and fear is increased in women compared to men (Bunt et al, 2020). Moreover, studies suggest that the severity of behavioral deficits in women depends on their menstrual phase (Bazarian et al, 2010;Stein, 2013;Wunderle et al, 2014).…”
Section: Behavioral Consequences Of Mild Tbimentioning
confidence: 98%
“…Male and female patients (N = 491) ages 12-18 with a diagnosed SRC within 30 days of a clinic visit (Bunt et al, 2020) Memory and concentration using the SCAT-5 scale Depression using GAD-7 Anxiety using PHQ-9…”
Section: Cognitive Emotionalmentioning
confidence: 99%
See 2 more Smart Citations
“…Several manuscript workgroups within the ConTex research team include premorbid risk factors, psychological factors in symptom maintenance, headache, sex differences,31 sleep32 and models for recovery prediction following SRC. A future goal of ConTex is to establish an effective framework for studies aiming to evaluate assessment, surveillance and treatment of concussion as well as the critical evaluation of diagnostic technologies as they are developed to advance the field of concussion research.…”
Section: Discussionmentioning
confidence: 99%